Chemistry Learning Material Solution Mixture Separation and Magnetic Separation - Utariningrum , Devy Zulfa (Balai Publikasi Indonesia, 2025)
In everyday life, a solution needs to be separated because the particles of solids that are not needed must be separated so they don't interfere with the solution or when taken or used they don't taste bad. Simple separation that can be done is separation using filter paper. Filter paper is a tool used to filter a mixture in the form of a solution through the pores of the filter paper which will leave residual solid particles on the filter paper. Meanwhile, magnetic separation is usually carried out in landfills (TPA) to separate metal, steel and iron objects from other objects besides that. Therefore, a simple experiment was carried out using simple tools, namely filter paper and magnets using simple materials, namely turmeric and paper clips as science learning. The purpose of the experiment was so that students could better understand the separation material